Relative age effect among world rugby under 20 championship 2019 players / Mohamad Izzudyn Fariss Mohd Hamizi and Jeffrey Fook Lee Low - Mohd Hamizi, Mohamad Izzudyn Fariss; Low, Jeffrey Fook Lee (Universiti Teknologi MARA, 2020)
This study aimed to investigate the presence of Relative Age Effects (RAE) with based on birth quartiles among the World Rugby Under 20 Championship 2019.Besides that, this study also determined the presence of RAE among present of one successful team and the unsuccessful team. Date of birth, height, weight, playing position from players (n=305) from all the 12 participating teams in the tournament were gathered from official websites. The players’ birth dates were categorized into four quartiles according to each country cut-off date. Countries such as Australia, New Zealand, South Africa, Argentina, Fiji, France, and Italy was set at 1st January, while for countries under United Kingdom (England, Wales and Scotland), Ireland and Georgia were set at 1st September. Chi squared goodness fit test was used to compare the distribution of players among the birth quartile and also the playing position and the team’s achievement (successful and unsuccessful). One-way ANOVA test was used to determine whether there were any statistical significant differences between the birth quartile and player’s height and weight. Presence of RAE was found in the overall position of rugby union players, and the teams that qualified for semis (deemed successful). Analysis on the playing positions found only the backline position showed presence of RAE but not among the forwards. Furthermore, there was no significant different between birth quartiles and player’s height and weight. As conclusion, the overrepresentation of relatively older players among World Rugby Under 20 Championship 2019 players were suggested due to the player’s selection process and playing roles according to nature of the sport.